Mobility Function and Recovery After Stroke: Preliminary Insights From Sympathetic Nervous System Activity. Issue 4 (October 2018) - Chatterjee, Sudeshna A.; Daly, Janis J.; Porges, Eric C.; Fox, Emily J.; Rose, Dorian K.; McGuirk, Theresa E.; Otzel, Dana M.; Butera, Katie A.; Clark, David J.
Abstract : Background and Purpose: Poststroke hemiparesis increases the perceived challenge of walking. Perceived challenge is commonly measured by self-report, which is susceptible to measurement bias. A promising approach to objectively assess perceived challenge is measuring sympathetic nervous system (SNS) activity with skin conductance to detect the physiological stress response. We investigated the feasibility of using skin conductance measurements to detect task-related differences in the challenge posed by complex walking tasks in adults poststroke. Methods: Adults poststroke (n = 31) and healthy young adults (n = 8) performed walking tasks including typical walking, walking in dim lighting, walking over obstacles, and dual-task walking. Measures of skin conductance and spatiotemporal gait parameters were recorded. Continuous decomposition analysis was conducted to assess changes in skin conductance level (ΔSCL) and skin conductance response (ΔSCR). A subset of participants poststroke also underwent a 12-week rehabilitation intervention. Results: SNS activity measured by skin conductance (both ΔSCL and ΔSCR) was significantly greater for the obstacles task and dual-task walking than for typical walking in the stroke group. Participants also exhibited "cautious" gait behaviors of slower speed, shorter step length, and wider step width during the challenging tasks. Following the rehabilitation intervention, SNS activity decreased significantly for the obstacles task and dual-task walking. Discussion and Conclusions: SNS activity measured by skin conductance is a feasible approach for quantifying task-related differences in the perceived challenge of walking tasks in people poststroke. Furthermore, reduced SNS activity during walking following a rehabilitation intervention suggests a beneficial reduction in the physiological stress response evoked by complex walking tasks. Video Abstract available for more insights from the authors (See Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A234 ). Abstract : Supplemental Digital Content is Available in the Text.